ANALISIS KELAYAKAN USAHA PENANGKAR BIBIT DURIAN (Durio zibethinus) PADA CV. KARYA TANI MANDIRI DI KABUPATEN LANGKAT - Lutfi Azhari Hasibuan; Siti Balqies Indra; Silvia Anzitha (Jurnal Inovasi Penelitian, 2023)
This study aims to analyze the feasibility of breeding Durian (Durio zibethinus) in CV. The Work of Independent Farmers in Langkat Regency. The sampling technique used was the purposive sampling method. Purposive Sampling is every subject taken from the population to be studied is selected deliberately based on certain goals and considerations. To find out whether the business is feasible or not, it can be used by analyzing the business by calculating production costs, calculating revenues, and analyzing results then calculating the results using the R/C Ratio and B/C Ratio methods. The results showed that the R/C Ratio value was 2.13 and the B/C Ratio value was 1.13, so it can be concluded that the durian seed breeding business at CV. Karya Tani Mandiri in Langkat Regency is feasible to run.